2018
DOI: 10.1007/s10548-018-0641-z
|View full text |Cite
|
Sign up to set email alerts
|

Action-Related Speech Modulates Beta Oscillations During Observation of Tool-Use Gestures

Abstract: Language and action have been thought of as closely related. Comprehending words or phrases that are related to actions commonly activates motor and premotor areas, and this comprehension process interacts with action preparation and/or execution. However, it remains unclear whether comprehending action-related language interacts with action observation. In the current study, we examined whether the observation of tool-use gesture subjects to interaction with language. In an electroencephalography (EEG) study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 55 publications
8
6
0
1
Order By: Relevance
“…During gesture perception, our results showed that frontal gestures elicited a more pronounced beta band power decrease than lateral gestures. This finding not only supports the role of the beta band oscillations for perception of hand actions in general (Angelini et al, 2018;Avanzini et al, 2012;Järveläinen et al, 2004), but also corroborates the sensitivity of the beta band power to the observation of different types of gestures (He et al, 2018a;Quandt et al, 2012). Previous studies that directly tested perceptual differences of body orientation or view point of non-communicative hand actions (e.g., reaching) also showed a modulated decrease of beta power (and alpha power) for more allocentric view point (Angelini et al, 2018;Drew et al, 2015).…”
Section: Social Perception Of Gesture's Body Orientationsupporting
confidence: 82%
See 1 more Smart Citation
“…During gesture perception, our results showed that frontal gestures elicited a more pronounced beta band power decrease than lateral gestures. This finding not only supports the role of the beta band oscillations for perception of hand actions in general (Angelini et al, 2018;Avanzini et al, 2012;Järveläinen et al, 2004), but also corroborates the sensitivity of the beta band power to the observation of different types of gestures (He et al, 2018a;Quandt et al, 2012). Previous studies that directly tested perceptual differences of body orientation or view point of non-communicative hand actions (e.g., reaching) also showed a modulated decrease of beta power (and alpha power) for more allocentric view point (Angelini et al, 2018;Drew et al, 2015).…”
Section: Social Perception Of Gesture's Body Orientationsupporting
confidence: 82%
“…However importantly, in the current study, although we observed an alpha band power decrease for both frontal and lateral gestures, unlike those studies examining non-communicative hand actions (Angelini et al, 2018;Drew et al, 2015), the alpha power did not differ between frontal and lateral orientation in our study. This data pattern attests to the hypotheses that alpha and beta power are dissociable during action or gesture observation, in the sense that alpha power decrease might be more related to sensory/motor perception in general, whereas the beta band is more sensitive to finegrained motor-related features (Brinkman et al, 2014;He et al, 2018a;Salmelin et al, 1995).…”
Section: Social Perception Of Gesture's Body Orientationsupporting
confidence: 82%
“…In addition, recent studies looking at the oscillatory domain of EEG also showed that both the alpha (8–13 Hz) and beta (14–26 Hz) bands may be functionally related to the integration between speech and communicative gesture (Biau, Torralba, Fuentemilla, de Diego Balaguer, & Soto‐Faraco, 2015; Drijvers, Özyürek, & Jensen, 2018a, 2018b; He et al, 2015; He, Steines, Sommer, et al, 2018). Interestingly, these frequency bands were also highly relevant to the perception of action and hand gestures in particular (Avanzini et al, 2012; He, Steines, Sammer, et al, 2018; Järveläinen, Schuermann, & Hari, 2004; Quandt, Marshall, Shipley, Beilock, & Goldin‐Meadow, 2012). It has been reported that gestures differing in social‐communicative intention (goal‐directed vs. non‐goal‐directed) (Hari et al, 1998; Järveläinen et al, 2004)—as well as the level of motor simulation (Quandt et al, 2012)—elicited differential level of alpha or beta band power decrease.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that gestures differing in social‐communicative intention (goal‐directed vs. non‐goal‐directed) (Hari et al, 1998; Järveläinen et al, 2004)—as well as the level of motor simulation (Quandt et al, 2012)—elicited differential level of alpha or beta band power decrease. Additionally, these effects may be even modulated by accompanying auditory speech, as in the case of co‐speech gesture (He, Steines, Sammer, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation